种适用于辉钼矿浮选尾矿中伴生白钨矿的选矿富集方法 (2018)
本发明提供种适用于辉钼矿浮选尾矿中伴生白钨矿的选矿富集方法，该方法包括：a、弱磁选和强磁选，b、非磁性矿浆物料粒级分级，c、重选，d、中矿再磨e、再分级重选等几个步骤，得到高品位高回收率的白钨精矿产品，使铜钼多金属混合共生矿中伴生的低品位白钨矿资源得到有效的综合回收利用。本发明方法，可较广泛地应用于共伴生低品位白钨矿资源的回收利用领域。 The invention provides a mineral separation and enrichment method suitable for associated scheelite in molybdenite floatation tailings. The method includes the steps of low-intensity magnetic separation, high-intensity magnetic separation, non-magnetic ore pulp material size fraction grading, gravity separation, middling regrinding, regrading gravity separation and the like. A high-grade and high-recovery scheelite concentrate product is obtained, the associated low-grade scheelite resource in Cu-Mo polymetallic mixed associated ore is effectively and comprehensively recovered and used. The method can be widely applied to the field of recovering and using the associated low-grade scheelite resource.